The use of structures of modification as a possible measure of language growth among students of Alejandro Roces High School and Manuel Roxas High School in Quezon City - Orencia, Elisa (Rejante) 1935- (1965)
This study is part of a group research underrtaken by twelve MAT (English as a second language) students which sought to discover a valid tool for measuring language growth. Specifically, it sought to find out whether there is a direct relationship between an increase of year level and the total structures of modification used.